2001
DOI: 10.1136/ard.60.4.310
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected cause of muscle pain in diabetes

Abstract: Diabetic muscle infarction is a rare condition which may present to a rheumatologist. It was first reported in 1965. Two illustrative cases are described here and the mechanisms of pathogenesis discussed. Analysis of the published data, results of the muscle biopsies, and a technetium-99m sestamibi scan suggest that the condition, which occurs against a background of diabetic microangiopathy, can be triggered by an ischaemic event and causes extensive muscle necrosis through hypoxia-reperfusion injury and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 29 publications
0
33
1
1
Order By: Relevance
“…3,4,[7][8][9] In diabetic patients, the well-known vascular changes-such as microangiopathy, atheroma embolization, or vascular occlusion with consequent muscle edema, which reduces capillary blood flow-may contribute to muscle injury. 9 One case series reported that idiopathic rhabdomyolysis often occurs in patients with liver cirrhosis and suggested that defective muscle metabolism due to hepatic dysfunction results in rhabdomyolysis in these patients. 8 Acute and chronic alcohol intoxication also has direct toxicity to muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,[7][8][9] In diabetic patients, the well-known vascular changes-such as microangiopathy, atheroma embolization, or vascular occlusion with consequent muscle edema, which reduces capillary blood flow-may contribute to muscle injury. 9 One case series reported that idiopathic rhabdomyolysis often occurs in patients with liver cirrhosis and suggested that defective muscle metabolism due to hepatic dysfunction results in rhabdomyolysis in these patients. 8 Acute and chronic alcohol intoxication also has direct toxicity to muscle.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 It has also been reported that the CPK levels were normal or mildly elevated in patients with diabetic muscle infarction. 9 Moreover, the diagnosis can also be made by plasma measurement of myoglobin levels even without measurement of CPK levels, 14 and some authors reported a case of rhabdomyolysis without describing the CPK levels. 15 We could not find evidence in the literature that CPK levels are always elevated in rhabdomyolysis cases.…”
Section: Discussionmentioning
confidence: 99%
“…The onset is usually acute, and spontaneously resolves after several weeks to months. 3 Recurrent episodes of muscle infarction in the same or a contralateral limb are reported to occur in half of patients, some of whom may have multiple recurrences. 4,5 The second patient developed a second attack nine years after the first in the same group of muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, considerable experience has accumulated through case reports and review of previously published cases. [2][3][4][5][6][7][8][9][10][11][12][13][14] Diabetic muscle infarction is a distinct entity with characteristic clinical and radiological findings. It is probably more common than previously recognized.…”
Section: Discussionmentioning
confidence: 99%
“…It can be triggered by an ischemic event and causes extensive muscle necrosis through hypoxia-reperfusion injury and compartment syndrome [2]. Angervall and Stener [3] first described muscle infarction in diabetic patients in 1965.…”
Section: Introductionmentioning
confidence: 99%